Tantangan dan Peluang Pendidikan Bahasa Arab: Perspektif Global - Manan, Abdul; Nasri, Ulyan (Jurnal Ilmiah Profesi Pendidikan, 2024)
Abstract: This research presents an in-depth analysis of challenges and opportunities in Arabic language education, with a focus on a global perspective. Arabic plays a crucial role on the international stage, serving not only as a religious language but also as a language of culture, science, and administration. However, Arabic language education in various countries faces several challenges that can impact the quality of learning and student comprehension. This literature review investigates some key challenges in Arabic language education, including non-aligned curricula, insufficient learning resources, and issues in developing Arabic language skills. Meanwhile, the research also highlights opportunities that can be utilized to enhance Arabic language education, such as the use of innovative educational technology, inter-institutional collaboration, and the promotion of cultural exchange programs. By analyzing various concepts and findings in related literature, this research provides profound insights into the global conditions of Arabic language education. By understanding the challenges faced and leveraging existing opportunities, effective strategies can be formulated to improve the quality of Arabic language education worldwide. This research is expected to contribute to the development of more holistic and sustainable Arabic language education policies, as well as motivate practical steps to enhance the teaching and learning of Arabic globally.